Random vibrations of a beam on elastic foundation - Faris, Waleed Fekry; Daoud, Jamal Ibrahim; Sutjipto, Agus Geter Edy (INSInet Publications, 2011)
Beam on an elastic foundation represents many applications like bridges, rail tracks. The analysis of such situation under dynamic loads is of quite importance to industry and researchers as well. Beam on elastic foundation represent a contact problem of the receding type. In this paper, we used a quasi-linear approach integrated with the Finite Element Method to model the contact problem. In this approach we exploit the standard form of the FEM for linear structures to solve a nonlinear problem instead of going into the nonlinear formulation. Then, we generate the random dynamic load using Monte-Carlo simulation. We study two different cases of beams on elastic foundation. We plot the displacement and velocity as outputs for this problem and analyze the input-output relationship from the randomness point of view.